Nineteenth-century religion, literature and society. - Dwor, Richa; Hetherington, Naomi, 1973- (Routledge, 2020)
Part of a four-volume set, this third volume looks at 'religious feeling' as an important and distinct category for understanding the ways in which religion is embodied and expressed in culture. The complete four-volume historical resource provides new opportunities for investigating the relationship between religion, literature and society in Britain and its imperial territories by making accessible a diverse selection of harder-to-find primary sources. These include religious fiction, poetry, essays, memoirs, sermons, travel writing, religious ephemera, unpublished notebooks and pamphlet literature. Spanning the long nineteenth century (c.1789-1914), the resource departs from older models of 'the Victorian crisis of faith' in order to open up new ways of conceptualising religion.
Keywords: Great Britain -- Religion -- 19th century -- Sources.; Emotions -- Religious aspects -- History -- 19th century -- Sources.; English literature -- 19th century -- History and criticism.; Religious literature, English -- 19th century -- History and criticism.; Religion and literature -- Great Britain -- History -- 19th century.; Religion in literature.; Grande-Bretagne -- Religion -- 19e siècle -- Sources.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Littérature religieuse anglaise -- 19e siècle -- Histoire et critique.; Religion et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Religion dans la littérature.; HISTORY -- Modern -- 19th Century.; Religion; Emotions -- Religious aspects; English literature; Religion and literature; Religion in literature; Religious literature, English; Great Britain; 1800-1899; Sources; Criticism, interpretation, etc.; History